Time and Society in the Qur'an: Al-Ghazali’s Integration of Ancient Wisdom into Islamic Epistemology - Mohammad Eisa Ruhullah; Thameem Ushama (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This research paper, titled explores the conceptualization of time in the Qur'an and its integration into Islamic epistemology through Al-Ghazali’s theoretical framework. The study addresses the research problem of how Qur'anic depictions of time intersect with contemporary scientific theories, particularly focusing on their implications for understanding the nature of time and its relevance to modern scientific and philosophical discussions. Utilizing a secondary descriptive analysis methodology, the research systematically reviews and compares Qur'anic verses about time with current scientific theories such as Einstein's theory of relativity and cosmological concepts. The aim is to identify points of convergence and divergence between Qur'anic insights and scientific understandings, enriching the discourse on the interplay between religious wisdom and empirical knowledge. The findings reveal a harmonious interaction between spiritual and scientific narratives, demonstrating that the Qur'an’s portrayal of time as a complex, relative phenomenon aligns with modern scientific perspectives. This integration of the Integration of Knowledge (IOK) concept fosters a holistic understanding of time, bridging theological and scientific viewpoints and contributing to broader discussions in political and democratic domains. The study underscores the significance of interdisciplinary knowledge in addressing societal issues and highlights the potential for mutual enrichment between ancient wisdom and contemporary science. Future research should continue to explore these intersections and their implications for education and societal development. Makalah penelitian ini mengeksplorasi konseptualisasi waktu dalam Al-Qur'an dan integrasinya ke dalam epistemologi Islam melalui kerangka teori Al-Ghazali. Penelitian ini membahas masalah penelitian tentang bagaimana penggambaran waktu dalam Al-Qur'an bersinggungan dengan teori-teori ilmiah kontemporer, terutama berfokus pada implikasinya untuk memahami sifat waktu dan relevansinya dengan diskusi ilmiah dan filosofis modern. Dengan menggunakan metodologi analisis deskriptif sekunder, penelitian ini secara sistematis meninjau dan membandingkan ayat-ayat Al-Qur'an tentang waktu dengan teori-teori ilmiah saat ini seperti teori relativitas Einstein dan konsep-konsep kosmologi. Tujuannya adalah untuk mengidentifikasi titik-titik konvergensi dan divergensi antara wawasan Al-Qur'an dan pemahaman ilmiah, memperkaya wacana tentang interaksi antara kebijaksanaan agama dan pengetahuan empiris. Temuan-temuan tersebut mengungkapkan interaksi yang harmonis antara narasi spiritual dan ilmiah, yang menunjukkan bahwa penggambaran Al-Qur'an tentang waktu sebagai fenomena yang kompleks dan relatif selaras dengan perspektif ilmiah modern. Integrasi konsep Integrasi Ilmu Pengetahuan (IOK) ini menumbuhkan pemahaman holistik tentang waktu, menjembatani sudut pandang teologis dan ilmiah serta berkontribusi pada diskusi yang lebih luas dalam domain politik dan demokrasi. Penelitian ini menggarisbawahi pentingnya pengetahuan interdisipliner dalam menangani masalah-masalah sosial dan menyoroti potensi untuk saling memperkaya antara kebijaksanaan kuno dan ilmu pengetahuan kontemporer. Penelitian di masa depan harus terus mengeksplorasi persimpangan ini dan implikasinya bagi pendidikan dan pembangunan masyarakat.